2012
DOI: 10.1155/2012/506302
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variation of N Isotopic Composition of Decomposing Legume Roots and Its Implications to N Cycling Estimates inN15Tracer Studies in Agroforestry Systems

Abstract: Below-ground residue of agroforestry trees is an important N source for associated crops. Several studies have shown that its isotopic signature (δ 15 N) may change after tree pruning, which makes it difficult to study below-ground N inputs from pruned trees by isotopic techniques. We studied how temporal variation of legume root residue δ 15 N could be explained by considering differential decomposition kinetics and 15 N content of residue fractions. A mathematical model on the isotopic patterns of soil and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Mathematical models have the potential to predict N flows at spatial and temporal scales that are beyond the capability of current experimental techniques. Certainly models have already been applied to examine aspects of isotopic fractionation (Shearer et al, 1974;Sierra and Desfontaines, 2011), and have previously been used in conjunction with the analysis of data derived from the use of 15 N enriched materials to describe the temporal variation in 15 N composition of decomposing legume material (Jalonen and Sierra, 2012) and the turnover of N through various plant, soil and microbial pools (Jenkinson and Parry, 1989), so similar approaches could be used to advance our knowledge. However, the construction and use of simulation models are only as good as the conceptual understanding of the individual processes and the values used to parameterize them (Jones et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematical models have the potential to predict N flows at spatial and temporal scales that are beyond the capability of current experimental techniques. Certainly models have already been applied to examine aspects of isotopic fractionation (Shearer et al, 1974;Sierra and Desfontaines, 2011), and have previously been used in conjunction with the analysis of data derived from the use of 15 N enriched materials to describe the temporal variation in 15 N composition of decomposing legume material (Jalonen and Sierra, 2012) and the turnover of N through various plant, soil and microbial pools (Jenkinson and Parry, 1989), so similar approaches could be used to advance our knowledge. However, the construction and use of simulation models are only as good as the conceptual understanding of the individual processes and the values used to parameterize them (Jones et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Given the potential size of below-ground pool of legume N and rhizosphere deposition of N (Fustec et al, 2010;Peoples et al, 2012), and reports that intercropping enhances root production and turnover of fine roots (Lehmann and Zech, 1998), a first approximation for N sources for transfer might more plausibly equate to a below-ground pathway of transfer of fixed N from the roots and/or nodules rather than above-ground sources of fixed N. This would particularly the case for annuals where opportunities for N contributions from foliage will be limited during a single growing season. Below-ground Bergersen et al (1988), Boddey et al (2000), Unkovich et al (2008Unkovich et al ( , 2000, and Unkovich ( 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 sources of N are also likely to be important in forage and agroforestry systems where above-ground parts are regularly harvested or pruned as this can induce senescence of nodules and roots (Vance et al, 1979;Sanginga et al, 1995;Jalonen and Sierra, 2012).…”
Section: Isotopic Fractionationmentioning
confidence: 99%
“…There have been issues, however, in using the technique with leguminous trees (Sierra and Daudin 2010). As Jalonen and Sierra (2012) assert, 15 N labelling may result in differential enrichment in different tree parts. The widespread use of juvenile trees in greenhouse studies (Rao and Giller 1993;Jalonen et al 2009a;Kurppa et al 2010;Isaac et al 2012) has been encouraged by the difficulty encountered in labelling large, mature trees via leaf feeding.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…For instance, charting the effects on N 2 -fixation and N transfer values by maximising reference plant physiological similarity while sacrificing environmental similarity, or vice versus, is required. Furthermore, recent work by Jalonen and Sierra (2012), which found that fractions of N 2 -fixing tree residue have unique δ 15 N values based upon their C/N ratios, exemplifies the detailed inquiry needed to obtain accurate N transfer estimates. They demonstrate the stochastic nature of δ 15 N; using mathematical models, 15 N patterns of the recipient plants were accurately simulated only when at least two fractions of residue with distinct δ 15 N signatures were included.…”
Section: Current Challengesmentioning
confidence: 95%